Analisis Tingkat Reliabilitas pada Item Tes Tipe Pilihan Ganda - Maulida Maulida; Silvi Puspa Widya Lubis (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
This study was designed to obtain a multiple choice type test instrument that conforms to the standard consist of reliability. This research was conducted from February to April 2014. The method used was qualitative descriptive with multiple choice test form used as many as 100 test items. Research subjects in this study as many as 43 students. The test is compiled and has been validated by a team of experts then given to the subject of research, then the data obtained analyzed reliability value. The results showed that the number of test items that have been valid as much as 70 test items and has high category reliability (rxx = 0.75). From the results of this study, it can be concluded that the test items developed have met the criteria of a good test, it is based on the category in the stage that has been implemented has been fulfilled all the conditions. The concept of osmosis, diffusion and cell organelle, especially mitochondria and chloroplasts are the most concepts of test items to be discarded.